1980
DOI: 10.1507/endocrj1954.27.supplement_157
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Motilin Secretion in the Postprandial State in Man

Abstract: The effect of various nutrients and hormones on motilin release was examined in normal volunteers and postvagotomy patients to investigate the mechanism of motilin secretion in the postprandial state. The ingestion of a mixed meal, protein and fat elevated the plasma motilin level, but the oral glucose load and arginine infusion lowered it. Although gastrin infusion showed no effect on the plasma motilin concentration, the infusion of insulin or glucagon inhibited motilin release in vivo. The patients, who und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 2 publications
3
12
0
Order By: Relevance
“…Ingestion of fat in vivo has been reported as a stimula tory factor [17,18], In our experiments, the mixture of mayonnaise, bile and pancreatic juice (10:1:1) did not stimulate motilin release. The concentration of bile in our test solution was probably too low to affect motilin release in itself.…”
Section: Perfusion Experimentssupporting
confidence: 45%
See 1 more Smart Citation
“…Ingestion of fat in vivo has been reported as a stimula tory factor [17,18], In our experiments, the mixture of mayonnaise, bile and pancreatic juice (10:1:1) did not stimulate motilin release. The concentration of bile in our test solution was probably too low to affect motilin release in itself.…”
Section: Perfusion Experimentssupporting
confidence: 45%
“…Vagal stimu lation [9], neural transmitters such as muscarinic agents [10,11], bombesin [12], and opiates [13], as well as lumi nal stimuli including alkalinization [14], acidification [15], pancreatic juice and bile [16] have been shown to increase motilin release. On the other hand, inhibitory factors also seem to exist, as suggested from experiments with intraduodenal glucose [17] and amino acids [18], intravenous somatostatin [ 19], and sham feeding (indirect vagal stimulation) [20], Almost all of the studies mentioned here were carried out in vivo, which means that it is difficult to distinguish between direct and indirect effects of the applied stimuli. Furthermore, motilin release in vivo shows a cyclic pat tern, perhaps a result of neurally mediated central control which can be difficult to control for.…”
Section: Introductionmentioning
confidence: 96%
“…Ingestion of a meal stimulated IR-VIP release, as reported by Burhol et al (1979), as it stimulates the release of gastrin, secretin, motilin, enteroglucagon, gastric inhibitory polypeptide (GIP) and somatostatin (Forell et al, 1971;Nilsson et al, 1972;Burhol et al, 1979;Saito et al, 1980;Ghatei and Bloom, 1981). Burhol et al (1980) also reported that intraduodenal infusion of bile stimulates the release of VIP, GIP and bicarbonate in man.…”
Section: Discussionmentioning
confidence: 69%
“…Although high doses of motilin could induce premature activity fronts in the fasting human (as in the dog), smaller doses of the exoge-nous peptide, injected to reproduce physiologic plasma increases, were active in only one of the four subjects in which it has been tested (8). Looking for an action of motilin during the digestive phase, Christofides et al (12), Saito et al (13), and Jenssen et al (14) concluded that motilin was released after the ingestion of a meal, but Rees et al (lo), Becker et al (15), and Collins et al (16) disagreed on this issue. On the other hand, Christofides et al (17) observed it could accelerate the gastric emptying rate while Ruppin et al (18) reported the opposite.…”
Section: Introductionmentioning
confidence: 99%